Volatile Fingerprints of Synthetic Wines Fermented by Different Oenological Yeast Strains - Sandra Pati; Ilaria Benucci; Giuseppe Rosiello; Marco Esti (Beverages)
Background: The role of the S. cerevisiae strain in defining the volatile fingerprint is expressed throughout alcoholic fermentation and post-fermentation sur lie aging and is crucial for customizing the wine style. Methods: In this study, the alcoholic fermentation was carried out in a synthetic must to exclusively bring out the performance of the yeast in terms of volatile compound production, excluding the effect of the grape. Results: Among the 33 volatile organic compounds identified in the synthetic wines by GC-MS, esters, alcohols, and acids, represented the major groups for the nine different commercial oenological strains tested. All the relevant differences in the volatile fingerprint of the synthetic wines, which were lab-scale fermented, were quantitative rather than qualitative. The clustergram representation of the volatiles revealed an outstanding fingerprint for two strains (VIN13 and VIN7) among those tested, featuring hexanoic acid, octanoic acid, the corresponding esters (ethyl hexanoate, ethyl octanoate), and the acetates (2-phenylethyl acetate, isoamyl acetate), all at the highest levels. No relationship was appreciated between the fermentation rate and the volatile fingerprints. Conclusions: The outcomes of this study address the wine industry’s needs, supplying a full characterization of a broad range of commercial yeasts’ ability in fermentative volatile production.